What Y Generation Think About Bandung Traditional Market - Maulida Yuliana; Fajar S. A Prabowo (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2018)
raditional market is a tool that becomes a benchmark in improving people's welfare. Community income also affects the level of purchases in traditional markets. Store image of traditional markets in generation Y is indispensable to assist local traders in determining their fate in the future. There are eight dimensions used to measure the store image of traditional markets in Bandung, amongst merchandise, sales personnel, store atmosphere, services, reputation, promotion, location, and facilities. Methods of collecting data are done through the distribution of questionnaires to generation Y who had visited the traditional market in the city of Bandung. From the distributed questionnaires, 389 questionnaires were obtained. Based on the results of data processing using the importance performance analysis, there are ten items whose performance can be maintained, three items become the top priority to be improved, eight items become the next priority, and the remaining two items can be reduced priority to repair. Based on the results of research, it is suggested for the manager of traditional markets in Bandung to focus on items that are in quadrant A. These items include circulation of movement in the market, market merchant services in the selection of merchandise, and parking facilities which found in Bandung traditional markets.